INHIBITORY ACTIVITY OF INDONESIAN MICROBIAL EXTRACTS AGAINST PROLIFERATION OF DLD-1 COLORECTAL CANCER CELL LINE - Ariza Yandwiputra Besari; Danang Waluyo; Tinta Komariyah; Erwahyuni Endang Prabandari (BRIN - Badan Riset dan Inovasi Nasional, 2023)
Colorectal cancer (CRC) is the second deadliest cancer in the world. Several anti-cancer agents are currently used for the clinical treatment of CRC. However, toxicity and drug resistance pose significant challenges in CRC chemotherapy. On the other hand, microbe-derived natural products have been explored as a source for the development of anti-cancer therapeutic agents. This study aimed to examine the potential of the microbial library in BioMCC (Biotech Center-BPPT Microbial Culture Collection) as a source for anti-cancer drug discovery. Among the 720 fungal extracts tested, 60 extracts (8.3%) showed inhibitory activity against the proliferation of the colorectal carcinoma DLD-1 cell line, while not affecting Vero cells (African green monkey kidney normal cell line). One of these active extracts was derived from the fungus Sporothrix sp. BioMCC-f.T.7716. Although the inhibitory mechanism of this extract against the proliferation of the DLD-1 cell line could not be determined, this study clearly demonstrated the potential use of Indonesian microbial extracts as a source for the discovery of anti-cancer agents.